2000
DOI: 10.1097/00000658-200001000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Early Wound Healing Exhibits Cytokine Surge Without Evidence of Hypoxia

Abstract: ObjectiveTo ascertain the spatial and temporal relation of wound hypoxia to the cell types involved, expression of selected angiogenic cytokines, the proliferative status of cells in the wound site, and angiogenesis. Summary Background DataHypoxia is considered to drive the angiogenic response by upregulating angiogenic cytokines observed during wound healing. But this correlation has not been shown on a cell-tocell basis in vivo because of limitations in measuring tissue PO 2 at the cellular level. MethodsUsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
2
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 49 publications
4
70
2
2
Order By: Relevance
“…However, it has been suggested that dual pathways are involved in the induction of HIF-1 within the wound bed. Pro-inflammatory mediators stimulate early expression, whereas, wound hypoxia becomes the major stimulus at later time points (20,22,23). The induction of HIF-1α expression at the wound site in the current study is related to the early inflammatory response and, in the excisional wound, animals correlated with a strong inflammatory response.…”
Section: Discussionmentioning
confidence: 46%
“…However, it has been suggested that dual pathways are involved in the induction of HIF-1 within the wound bed. Pro-inflammatory mediators stimulate early expression, whereas, wound hypoxia becomes the major stimulus at later time points (20,22,23). The induction of HIF-1α expression at the wound site in the current study is related to the early inflammatory response and, in the excisional wound, animals correlated with a strong inflammatory response.…”
Section: Discussionmentioning
confidence: 46%
“…There is a normal tissue corollary to this, based on wound healing. In a rat dermal skin wound model, hypoxia was not involved in the initiation of angiogenesis; rather, it was associated with the period of wound involution after reepithelialization 14 . In an analogous fashion, HIF1 upregulation and increases in VEGF in response to tumour hypoxia may be important in vascular remodelling during continued tumour growth 128 .…”
Section: Hypoxia and Angiogenesismentioning
confidence: 99%
“…Examples of relatively hypoxic normal tissues include pericentral vein cells in the liver 12 , portions of the retina (in the dark) 13 , spinous layer of the epidermis 14 , the thymus 6,15 , renal tubular epithelium 16 , myocardium (particularly during exercise) 17 and subregions of the bone marrow that are enriched for stem cells 18 . Hypoxia has diverse roles in the function of these normal tissues.…”
Section: Regulation Of Hif1 By Hypoxiamentioning
confidence: 99%
“…This led some to suggest that hypoxia (and other stress factors such as pH and glucose availability) might be essential for promoting angiogenesis and other repair mechanisms in wound healing (58). However, Haroon et al (59) used PIMO labeling to show that hypoxia was largely absent on day 1 after punch biopsy wounds had been created in rats. Macrophages expressing various proangiogenic cytokines were found in these early, nonhypoxic lesions.…”
Section: Woundsmentioning
confidence: 99%